Kontrola ryzyka w planowaniu i wdrażaniu projektów logistycznych - Klopott, Magdalena (Risk Control in Planning and Implementation of Logistic Projects, 2008)
The characteristic feature of every logistic project is a high level of risk and uncertainty. Hence the risk management programme including the risk evaluation as well as selection of appropriate method of handling risks, also risk control, is often a decisive factor which could make logistic project successful. This paper presents risk control methods in logistic projects (risk avoidance, risk reduction, risk control transfer) and accident theories which form the basis for this. The necessity of contingency planning is also pointed. Theoretical discussion is illustrated by practical examples of risk control techniques.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 99-106